A randomized controlled study on the effect of intermittent theta burst stimulation on craving, mood, and cognitive function in alcohol-dependent patients during the withdrawal period - WANG Haihong; YUAN Chenxin; GAN Hong; JIANG Haifeng; ZHAO Yan; DU Jiang; ZHANG Yi (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To explore the effect of intermittent theta burst stimulation (iTBS) targeting the left dorsolateral prefrontal cortex (DLPFC) on reducing craving in alcohol-dependent patients during the withdrawal period, as well as its impact on patients' emotions and cognitive functions.Methods·A total of 41 inpatients with alcohol dependence in the withdrawal period were recruited from the Addiction Department of Mental Health Center, Shanghai Jiao Tong University School of Medicine, and randomly assigned to the experimental group (20 patients) and the control group (21 patients). Both groups received routine inpatient treatment for alcohol-dependence. The experimental group received real iTBS stimulation targeting the left DLPFC on the basis of routine inpatient treatment, while the control group received sham stimulation with the same parameters. The intervention course lasted for 2 weeks, with a total of 10 sessions. The Visual Analogue Scale (VAS), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were used to measure the craving, anxiety, and depression of the patients before and after the intervention. The behavioral tasks of the detection task (DET), identification task (IDN), two back task (TWOB), the Groton maze learning task (GML), and international shopping list task (ISL) in the CogState software package were used to assess the cognitive processing speed, attention/vigilance, working memory, spatial problem-solving/error monitoring ability, and verbal learning and memory of the patients before and after the intervention.Results·Repeated measures ANOVA showed that the time effect [F=126.713, P<0.001, partial η² (ηp2)=0.765] and interaction effect (F=7.080, P=0.011, ηp2=0.154) of the VAS scores in the two groups of patients were statistically significant. The time effect (F=9.114, P=0.004, ηp2=0.189), group effect (F=5.557, P=0.024, ηp2=0.125), and interaction effect (F=4.977, P=0.032, ηp2=0.113) of the TWOB score were all statistically significant. Only the time effects of BDI (F=45.273, P<0.001, ηp2=0.578), BAI (F=31.432, P<0.001, ηp2=0.473), GML (F=8.993, P=0.005, ηp2=0.209), and ISL (F=26.657, P<0.001, ηp2=0.439) scores were statistically significant. There were no statistically significant effects of time, group, or interaction on the DET and IDN scores. Simple effect analysis showed that the VAS score of the real stimulation group was lower than that of the sham stimulation group after the intervention (F=8.805, P=0.005, ηp2=0.184), and the TWOB score of the real stimulation group was higher than that of the sham stimulation group (F=11.293, P=0.002, ηp2=0.225).Conclusion·Combining iTBS with routine inpatient treatment can enhance the efficacy of reducing alcohol craving in alcohol-dependent patients during the withdrawal period, and improve their working memory.